Earth: The Nexus of Science, Spirituality, and Societal Strife - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
Earth serves as a hub for the convergence of science, spirituality, and social dynamics, which shapes our knowledge of the planet and its future. We look at how these aspects are related and what that means for sustainability and environmental stewardship in this multidisciplinary investigation. We reveal the intricate relationship between human activity and the Earth's ecosystems, underscoring the pressing need for comprehensive solutions. We base our findings on scientific research, spiritual beliefs, and societal viewpoints. Collaboration across all fields and businesses is necessary to address the issues facing our planet, which include plastic pollution in our oceans, deforestation, and climate change. Advocating for legislative changes, fostering interfaith understanding, advancing environmental education, and supporting sustainable development efforts, can empower individuals and groups to confront environmental challenges and build a more resilient and peaceful connection with the planet.